Hidrolisis Eceng Gondok (Eichhornia Crassipes) Menjadi Glukosa Menggunakan Rotating Microwave Reactor - Sarah, Maya; Pratiwi, Ita; Hasibuan, Isti Madinah (Talenta Publisher (Universitas Sumatera Utara), 2022)
Water hyacinth is lignocellulosic biomass that has the potential for glucose production because it contains 64.51% cellulose. Hydrolysis of water hyacinth was done in a rotating reactor with a microwave as a heat source. This study aims to obtain glucose by determining the hydrolysis reaction rate constant of power and sulfuric acid (H2SO4) concentration function and to find the best conditions for this hydrolysis process. Several research variables were H2SO4 concentration (0.5 N; 1 N; and 1.5 N), microwave power (600 W and 800 W) and reaction time of 60 minutes. Parameters measured were hydrolyzate temperature, glucose, and cellulose content. The hydrolysis reaction rate constant obtained based on the Arrhenius equation wasÂ k =1.30 x 10-2 e-132.172/T and the relationship between H2SO4 concentration and microwave power was C = 0.001P. The best conditions were obtained using 1 N H2SO4 and microwave power of 600 W with final glucose content of 486 mg/L.